A study of crime potentials in Taman Melati terrace housing in Kuala Lumpur : issues and challenges - Mohit, Mohammad Abdul; Hannan, Mohamed Hassan Elsawahli (Elsevier, 2012)
Recently, Malaysia has adopted “Safe city programme”, which is focused towards creating violence and crime free cities. To achieve this, it is important to address crimes and disorder in residential areas. So far studies identified thatchanges in built environment and modifications in space design can impact residents and offenders perceptions of criminality. Various CPTED measures are employed to create defensible space. This paper examines the effects of physical design on the occurrences of crime in Taman Melati residential area of Kuala Lumpur City and tests the effects of the built environment on the possibility of crime reduction through physical planning measures.